Symbol

# Calculator search results

Formula
Solve the system of equations
Graph
$7 \left ( 4 + x \right ) = 2 \left ( y - 3 \right )$
$4 \left ( - x - y \right ) = 7 - y$
$x$Intercept
$\left ( - \dfrac { 34 } { 7 } , 0 \right )$
$y$Intercept
$\left ( 0 , 17 \right )$
$x$Intercept
$\left ( - \dfrac { 7 } { 4 } , 0 \right )$
$y$Intercept
$\left ( 0 , - \dfrac { 7 } { 3 } \right )$
$\begin{cases} 7 \left( 4+x \right) = 2 \left( y-3 \right) \\4 \left( -x-y \right) = 7-y \end{cases}$
$x = - 4 , y = 3$
Solve the system of equations
$\begin{cases} \color{#FF6800}{ 7 } \left ( \color{#FF6800}{ 4 } \color{#FF6800}{ + } \color{#FF6800}{ x } \right ) = \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) \\ \color{#FF6800}{ 4 } \left ( \color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ y } \right ) = \color{#FF6800}{ 7 } \color{#FF6800}{ - } \color{#FF6800}{ y } \end{cases}$
 Organize the expression 
$\begin{cases} \color{#FF6800}{ 28 } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \color{#FF6800}{ x } = \color{#FF6800}{ 2 } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 6 } \\ \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ y } = \color{#FF6800}{ 7 } \color{#FF6800}{ - } \color{#FF6800}{ y } \end{cases}$
$\begin{cases} 28 + 7 x = 2 y - 6 \\ - 4 x - 4 y = 7 - y \end{cases}$
 Solve a solution to $x$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 } { 7 } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 34 } { 7 } } \\ - 4 x - 4 y = 7 - y \end{cases}$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 } { 7 } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 34 } { 7 } } \\ \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ y } = \color{#FF6800}{ 7 } \color{#FF6800}{ - } \color{#FF6800}{ y } \end{cases}$
 Substitute the given $x$ value into the equation $- 4 x - 4 y = 7 - y$
$\color{#FF6800}{ - } \color{#FF6800}{ 4 } \left ( \color{#FF6800}{ \dfrac { 2 } { 7 } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 34 } { 7 } } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ y } = \color{#FF6800}{ 7 } \color{#FF6800}{ - } \color{#FF6800}{ y }$
$\color{#FF6800}{ - } \color{#FF6800}{ 4 } \left ( \color{#FF6800}{ \dfrac { 2 } { 7 } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 34 } { 7 } } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ y } = \color{#FF6800}{ 7 } \color{#FF6800}{ - } \color{#FF6800}{ y }$
 Solve a solution to $y$
$\color{#FF6800}{ y } = \color{#FF6800}{ 3 }$
$\color{#FF6800}{ y } = \color{#FF6800}{ 3 }$
 Substitute the given $y$ value into the equation $x = \dfrac { 2 } { 7 } y - \dfrac { 34 } { 7 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 } { 7 } } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 34 } { 7 } }$
$x = \color{#FF6800}{ \dfrac { 2 } { 7 } } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } - \dfrac { 34 } { 7 }$
 Calculate the product of rational numbers 
$x = \color{#FF6800}{ \dfrac { 6 } { 7 } } - \dfrac { 34 } { 7 }$
$x = \color{#FF6800}{ \dfrac { 6 } { 7 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 34 } { 7 } }$
 Find the difference between the two fractions $\dfrac { 6 } { 7 }$ and $- \dfrac { 34 } { 7 }$
$x = \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
 The possible solutions are as follows 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 } , \color{#FF6800}{ y } = \color{#FF6800}{ 3 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 } , \color{#FF6800}{ y } = \color{#FF6800}{ 3 }$
 Check if it is the solution to the system of equations 
$\begin{cases} \color{#FF6800}{ 7 } \left ( \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) = \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) \\ \color{#FF6800}{ 4 } \left ( \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = \color{#FF6800}{ 7 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \end{cases}$
$\begin{cases} \color{#FF6800}{ 7 } \left ( \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) = \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) \\ \color{#FF6800}{ 4 } \left ( \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = \color{#FF6800}{ 7 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \end{cases}$
 Simplify the equality 
$\begin{cases} \color{#FF6800}{ 0 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ 4 } = \color{#FF6800}{ 4 } \end{cases}$
$\begin{cases} \color{#FF6800}{ 0 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ 4 } = \color{#FF6800}{ 4 } \end{cases}$
 Since it is true in both equations, it is the solution of the system of equations 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 } , \color{#FF6800}{ y } = \color{#FF6800}{ 3 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture